2015
DOI: 10.1007/s10457-015-9829-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of biological, chemical and mechanical treatments on sesquiterpene content in stems of planted Aquilaria crassna trees

Abstract: Agarwood trade has been growing rapidly due to its active ingredients composed of volatile substances, which are widely used in the cosmetics and pharmaceuticals. However, the formation time of agarwood in nature is quite long and little is known about its formation agents and mechanisms in planted Aquilaria crassna trees. In this study, biological, chemical and mechanical treatments were applied to 5-, 8-, and 11-year-old A. crassna plantations in north central, Vietnam. Agarwood samples were collected at 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Instead of relying on external stimuli to trigger plant responses, either by mechanical wounding or biological inoculum, some induction approaches have been developed to introduce signaling molecules directly and specifically into Aquilaria trees to initiate agarwood resin biosynthesis pathways (Liu Y. et al, 2013; Wu et al, 2017). Chemical inducers normally comprise of phytohormones, salts, minerals and biological-derived substances (Zhang et al, 2012; Liu Y. et al, 2013; Van Thanh et al, 2015). Besides, suitable delivery method is often developed together with the chemical formulations to ease the large-scale induction process, such as vessel equipped with transfusion needle (Yang et al, 2014c).…”
Section: Agarwood Induction Approachesmentioning
confidence: 99%
“…Instead of relying on external stimuli to trigger plant responses, either by mechanical wounding or biological inoculum, some induction approaches have been developed to introduce signaling molecules directly and specifically into Aquilaria trees to initiate agarwood resin biosynthesis pathways (Liu Y. et al, 2013; Wu et al, 2017). Chemical inducers normally comprise of phytohormones, salts, minerals and biological-derived substances (Zhang et al, 2012; Liu Y. et al, 2013; Van Thanh et al, 2015). Besides, suitable delivery method is often developed together with the chemical formulations to ease the large-scale induction process, such as vessel equipped with transfusion needle (Yang et al, 2014c).…”
Section: Agarwood Induction Approachesmentioning
confidence: 99%
“…The identities of chemicals in patents are generally not made public, or their strengths and formulations are kept discrete. They could be in the form of plant defense elicitors such as hydrogen peroxide (H 2 O 2 ), methyl jasmonate (MJ), or salicylic acid (SA) (Okudera and Ito 2009 ;Wijitphan 2009 ;Wei et al 2010 ) or chemicals such as sodium chloride, sulfuric acid, formic acid, and sodium methyl bisulfi te (Thanh et al 2015 ). Chemical-based inducer acts by causing severe injury to Aquilaria cell structure, and as a result callusing cannot be performed to cover up the wound.…”
Section: Chemical As Inducermentioning
confidence: 99%
“…Another important factor is the treatment applied onto the tree to induce agarwood. In a fi eld trial conducted in planted A. crassna , Thanh et al ( 2015 ) showed that agarwood oil samples from different treatments including biological (fungal mixture), chemical (sulfuric acid and sodium methyl bisulfi te mixture), and mechanical (hammered nails) differ in quantity and quality. A year after, chemical treatment yielded agarwood oil with the highest sesquiterpene content compared to the other treatments and non-treated.…”
Section: Factors Infl Uencing Agarwood Yield and Qualitymentioning
confidence: 99%
“…The physical or mechanical manipulations have usually been performed by wounding, boring, or nailing, but agarwood formation in response to these treatments still takes a long time and was of poor quality (Liu et al 2013). Chemical agents, such as jasmonic acid (Xu et al 2016), methyl jasmonate, salicylic acid (Okudera and Ito 2009), sulphuric acid (Thanh et al 2015), and hydrogen peroxide (Lv et al 2019) have also been tried. These treatments did induce agarwood formation in a relatively shorter time than in the wild but there are environmental concerns about their use (Turjaman et al 2016).…”
Section: Introductionmentioning
confidence: 99%